2015
DOI: 10.1007/s13277-015-4611-8
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-137 is downregulated in thyroid cancer and inhibits proliferation and invasion by targeting EGFR

Abstract: microRNA-137 expression is downregulated in several tumors. To date, its expression and function in human thyroid cancer remain unexplored. The aim of this study is to identify its expression, function, and molecular mechanism in thyroid cancer. microRNA-137 (miR-137) downregulation was observed in thyroid cancer tissues compared with normal thyroid tissues. miR-137 mimics downregulated B-CPAP cell proliferation, colony formation ability, and invasion, with suppressed expression of cyclin E, MMP2, p-ERK, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Moreover, Src induced the activation of the p38-MAPK/JNK signaling pathway in CD34+ cells [ 31 ]. Thyroid cancer cells transfected with miR-137 mimics showed a reduction in p-ERK and p-AKT [ 32 ], suggesting a negative correlation between miR-137 and the MAPK signaling pathway. These results support our conclusion that miR-137 suppressed ischemic stroke progression by targeting Src gene thus blocking the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Src induced the activation of the p38-MAPK/JNK signaling pathway in CD34+ cells [ 31 ]. Thyroid cancer cells transfected with miR-137 mimics showed a reduction in p-ERK and p-AKT [ 32 ], suggesting a negative correlation between miR-137 and the MAPK signaling pathway. These results support our conclusion that miR-137 suppressed ischemic stroke progression by targeting Src gene thus blocking the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-137 is downregulated in thyroid carcinoma and acts as a tumor suppressor by targeting Stromal cell-derived factor 1 and epidermal growth factor receptor (17,18). It can also improve the dexamethasone sensitivity in multiple myeloma cells via inhibition of microphthalmia-associated transcription factor as well as the Akt signaling pathway (6).…”
Section: Discussionmentioning
confidence: 99%
“… 13 Located on chromosome 1p22, 14 miR-137 has attracted much attention because it is frequently downregulated in cancer tissues, such as ovarian cancer, 15 gastric cancer, 16 colorectal cancer, 17 non-small-cell lung cancer, 18 and neuroblastoma. 19 It has also been reported that miR-137 can suppress invasion in thyroid cancer, 20 non-small-cell lung cancer, 18 and breast cancer. 21 Our previous studies indicated that miR-137 expression in BC tissues is almost undetectable in comparison to their adjacent non-tumorous bladder urothelium.…”
Section: Introductionmentioning
confidence: 97%